Istihsan in Matters of Faith: A Practical Study of the Principles - Mansour, Mohamed Khaled (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This research examines jurists’ use of Istihsan in oaths, its explicit references, and practical applications for alleviation. It explores its meaning, causes, and impact on explicit and derived rulings of oaths and expiation. Methods: The nature of this research necessitated adopting the inductive approach to examine juristic texts related to the issues of oaths and the expiation of binding oaths, analyzing them to determine the essence of Istihsan in this domain, and comparing these texts. Additionally, the deductive approach was employed to establish the foundational principles of Istihsan in oaths, deducing its rules, criteria, causes, and types. Results: One of the key findings of this research is that Istihsan in oaths serves as a methodological and foundational legal tool that allows for exceptions to general rules to achieve facilitation and alleviation, in line with the legislator’s intent regarding oaths and expiation. The research also highlights that jurists gave significant attention to Istihsan in oaths and expiation, particularly in the Hanafi school, followed by the Maliki and Shafi’i schools, while it was relatively less emphasized in the Hanbali school. Conclusion: This research was based on the principles of establishing and deducing Istihsan as a foundational methodology in the domain of oaths, examining its applications and orientations among jurists.